Quasi-static Eocene-Oligocene climate in Patagonia promotes slow faunal evolution and mid-Cenozoic global cooling - Kohn, Matthew J. (2015)
New local/regional climatic data were compared with floral and faunal records from central Patagonia to investigate how faunas evolve in the context of local and global climates. Oxygen isotope compositions of mammal fossils between c. 43 and 21 Ma suggest a nearly constant mean annual temperature of 16 ± 3 °C, consistent with leaf physiognomic and sea surface studies that imply temperatures of 16–18 °C. Carbon isotopes in tooth enamel track atmospheric δ 13 C, but with a positive deviation at 27.2 Ma, and a strong negative deviation at 21 Ma. Combined with paleosol characteristics and reconstructed Leaf Area Indices (rLAIs), these trends suggest aridification from 45 Ma (c. 1200 mm/yr) to 43 Ma (c. 450 mm/yr), quasi-constant MAP until at least 31 Ma, and an increase to ~ 800 mm/yr by 21 Ma. Comparable MAP through most of the sequence is consistent with relatively constant floral compositions, rLAI, and leaf physiognomy. Abundance of palms reflects relatively dry-adapted lineages and greater drought tolerance under higher p CO2 . Pedogenic carbonate isotopes imply low p CO2  = 430 ± 300 ppmv at the initiation of the Eocene–Oligocene climatic transition. Arid conditions in Patagonia during the late Eocene through Oligocene provided dust to the Southern Ocean, enhancing productivity of silicifiers, drawdown of atmospheric CO 2 , and protracted global cooling. As the Antarctic Circumpolar Current formed and Earth cooled, wind speeds increased across Patagonia, providing more dust in a positive climate feedback. High tooth crowns (hypsodonty) and ever-growing teeth (hypselodonty) in notoungulates evolved slowly and progressively over 20 Ma after initiation of relatively dry environments through natural selection in response to dust ingestion. A Ratchet evolutionary model may explain protracted evolution of hypsodonty, in which small variations in climate or dust delivery in an otherwise static environment drive small morphological shifts that accumulate slowly over geologic time.